Different determinants of sprint swim performance in male and female competitive swimmers - Simmons, S. E.; Tanner, D. A.; Stager, J. M. (Medicine & Science in Sports & Exercise, 2000)
The relationship between muscular power and swimming velocity in both genders was evaluated. Competitive swimmers (M = 139; F = 122) were measured for age, height, weight, body mass index, medicine ball chest pass, vertical jump, peak force and mean force from a 30-second tethered swim test, a 15-yard timed swim, and best competitive time for 50-m freestyle.